Evaluation of Air Quality Model Performance for Simulating Long-Range Transport and Local Pollution of PM2.5 in Japan - Hikari Shimadera; Tatsuya Kojima; Akira Kondo (Advances in Meteorology)
The Community Multiscale Air Quality Model (CMAQ) v5.0.2 was applied to PM2.5 simulation in Japan, which is strongly affected by long-range transport (LRT) from anthropogenic sources in the Asian Continent, for one year from April 2010 to March 2011. The model performance for LRT and local pollution (LP) of PM2.5 was evaluated to identify the model processes that need to be improved. CMAQ well simulated temporal and spatial variation patterns of PM2.5 but underestimated the concentration level by 15% on average. The contribution of LRT was estimated from the difference between the baseline simulation case and a zero-emission case for anthropogenic emissions in the continent. The estimated LRT contribution to PM2.5 was 50% on average and generally higher in the western areas of Japan (closer to the continent). Days that were dominantly affected by LRT or LP were determined based on the contribution of LRT to sulfate, which was fairly well simulated and strongly affected by LRT among major PM2.5 components. The underestimation of PM2.5 was larger in LP days (by 26% on average) than LRT days (by 10% on average). Therefore, it is essential to improve local emissions, formation, and loss processes of precursors and PM2.5 in Japan.